Looking at scientific research of HEI through the lens of the SDGs - Simaens, A.; Rato, V.; Roseta-Palma, C.; Farelo, C. (5th Responsible Management Education Research Conference, 2018)
The role of Higher Education Institutions (HEI) in the promotion of sustainability is indisputable (e.g. Figueiró and Raufflet, 2015, Stephens et al., 2008, Cortese, 2003). The Sustainable Development Goals (SDGs), agreed upon in 2015, have reinforced the opportunities for HEI to provide valuable contributions, as recognized in international fora (e.g. PRME and HESI). Velazquez et al. (2006) refer to a sustainable university as a “Higher education institution, as a whole or as a part, that addresses, involves and promotes, on regional or global level, the minimization of environmental, economics, societal and health negative effects in the use of their resources in order to fulfil its main functions of teaching, research, outreach & partnership, and stewardship among others as a way to helping society make the transition to sustainable life styles.” Hence, this work relies on the premise that HEI have a unique role as promoters and diffusers of these goals of critical importance for humanity and the planet, through teaching, research and knowledge transfer. Also, it stresses that the outreach capacity of these academic processes can overcome the potentially negative impacts of campus operations. For the purpose of this work we focus on research. We aim to explore whether and to what extent HEI are deliberately developing scientific publications that address the 17 SDGs. We explore this by taking stock of the scientific research conducted at a Portuguese HEI, ISCTE-IUL, and particularly its Business School, on the topics related to the SDGs and published in the period 2015-2017. Through content analysis, this work presents an exploratory analysis of a case study on the diffusion of scientific knowledge related to the greatest global challenge of sustainable development. The main conclusion is that using the lens of the SDGs in analysing the extant research provides a holistic approach to our understanding of Sustainability and of our potential positive impact as researchers towards Sustainability.